Comprensión y resolución de problemas matemáticos desde la macroestructura del texto - Montero, Leidi Viviana; Mahecha, Jair Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2020)
A concern in primary school teachers in Colombia, is the poor performance of students in mathematics and in the state tests, because although there is aptitude in the solution of algorithms, there is difficulty in the processes of understanding the enounce math problems. The main purpose of this article is to share a methodological proposal that contributes to the improvement of the levels of understanding and resolution of mathematical problems, from the concept of textual macrostructure, integrating the areas of mathematics and Language. The qualitative research process was developed within the framework of action research; it had the theoretical review and rationale and three key phases: the diagnosis, the analysis of the information and, based on these two, the elaboration of the methodological proposal. As main results is presented: The diagnosis of difficulties and strengths when solving mathematical problems, the design of the methodological proposal integrating the reconstruction of macrostructures in the analysis of statements, and the principle interdependence between mathematics and language.